Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1371/journal.pone.0276241
|View full text |Cite
|
Sign up to set email alerts
|

Cellular interferon-gamma and interleukin-2 responses to SARS-CoV-2 structural proteins are broader and higher in those vaccinated after SARS-CoV-2 infection compared to vaccinees without prior SARS-CoV-2 infection

Abstract: Class I- and Class II-restricted epitopes have been identified across the SARS-CoV-2 structural proteome. Vaccine-induced and post-infection SARS-CoV-2 T-cell responses are associated with COVID-19 recovery and protection, but the precise role of T-cell responses remains unclear, and how post-infection vaccination (‘hybrid immunity’) further augments this immunity To accomplish these goals, we studied healthy adult healthcare workers who were (a) uninfected and unvaccinated (n = 12), (b) uninfected and vaccina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 70 publications
3
4
0
Order By: Relevance
“…All participants had detectable T cell responses for up to 6 months after the booster dose, consistent with previous research 15 . In parallel with other studies, T cell responses after COVID-19 vaccination were mainly directed to the S antigen 49 , with the secretion of IFN-γ, followed by IL-2 50,51 . SARS-CoV-2-specific CD4 + T cells had a central and effector memory phenotype [52][53][54] , while CD8 + T cells were predominantly naïve-like and terminal effector memory [54][55][56] .…”
Section: Discussionsupporting
confidence: 79%
“…All participants had detectable T cell responses for up to 6 months after the booster dose, consistent with previous research 15 . In parallel with other studies, T cell responses after COVID-19 vaccination were mainly directed to the S antigen 49 , with the secretion of IFN-γ, followed by IL-2 50,51 . SARS-CoV-2-specific CD4 + T cells had a central and effector memory phenotype [52][53][54] , while CD8 + T cells were predominantly naïve-like and terminal effector memory [54][55][56] .…”
Section: Discussionsupporting
confidence: 79%
“…Although we did not nd differences among T-cell responses to peptides pools, likely due to the small sample size for this analysis, other studies have shown higher IFN-γ and IL-2 responses to the S, M, and N proteins in previously infected and vaccinated individuals compared with those in uninfected participants after mRNA vaccines 56 . Moreover, previous studies have suggested that prior SARS-CoV-2 infection enhances immune responses to S, N, and M proteins after vaccination 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have highlighted the importance of IFN-γ measurement in understanding vaccine efficacy, immune system activation, and predicting immune responsiveness [53,54]. In particular, for SARS-CoV-2, vaccine-induced protection requires an IFN-γ-driven cellular immune response [55,56]. In this study, high levels of IFN-γ were observed in mice immunized with TMV (-A, -D, and -H), suggesting that these constructs may elicit a robust T-cell response that may activate the cellular arm of the immune system.…”
Section: Discussionmentioning
confidence: 99%